2012
DOI: 10.1108/01443571211230943
|View full text |Cite
|
Sign up to set email alerts
|

The impact of external institutional drivers and internal strategy on environmental performance

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(101 citation statements)
references
References 60 publications
6
93
0
2
Order By: Relevance
“…some scholars argue that external pressures lead to the symbolic implementation of the standard (Boiral 2007;Castka and Prajogo 2013), while others suggest that the intensity of external pressures increases the internalization of the standard (Christmann and Taylor 2006;Zailani et al 2012). Despite the fruitful insights it offers, this literature does not take into account that external pressures may have a qualified impact on firms' internal motivations to implement ISO 14001.…”
Section: Discussion and Research Implicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…some scholars argue that external pressures lead to the symbolic implementation of the standard (Boiral 2007;Castka and Prajogo 2013), while others suggest that the intensity of external pressures increases the internalization of the standard (Christmann and Taylor 2006;Zailani et al 2012). Despite the fruitful insights it offers, this literature does not take into account that external pressures may have a qualified impact on firms' internal motivations to implement ISO 14001.…”
Section: Discussion and Research Implicationsmentioning
confidence: 95%
“…Research by Zailani et al (2012), for instance, identifies governments as among the main external drivers that increase the use of internal proactive environmental strategies such as ecodesign. However, other studies question the influence of external factors and maintain that government pressures might encourage firms to adopt ISO 14001, but may not be sufficient to make companies implement the standard in a substantive way (Lannelongue et al 2013).…”
Section: External and Internal Factors Influencing Iso 14001 Implemenmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanim Mohamad Zailani et al [274] EMS ISO 14001-certified manufacturing firms 132 Firms Institutional theory…”
Section: Purchasing Managersmentioning
confidence: 99%
“…The results of this paper found that GP practices affected firm performance and technical aspects. Table A7 (see Appendix A) mentioned the analysis of 28 studies [265][266][267][268][269][270][271][272][273][274][275][276][277][278][279][280][281][282][283] regarding green and sustainable operation management based on the author(s) names, year of publication scope and sample of study, area of study, number of sample, respondents, related theory, variables, study purpose, gap and research problem and results and outcome.…”
Section: Breakdown Of Articles Based On Other Green and Sustainable Omentioning
confidence: 99%